Natural and artificial bodies in early modern England - Snider, Alvin Martin, 1954- author. Link
1 online resource (ix, 215 pages)
Keywords: "This book brings contemporary ways of reconceptualizing the human relationship to things into conversation with seventeenth-century writing, exploring how the literature of the period intersected with changing understandings of the conceptual structure of matter, and how human beings might reconfigure their place in a web of non-human relations. Focusing on texts that cross the frontier between literature and science, Snider recovers the material and body worlds of seventeenth-century culture as treated in poetry, natural philosophy, medical treatises, comedy, and prose fiction. He shows how a range of writers understood and theorized "matter," "bodies," and "spirits" as characters in complex and sometimes bizarre scenarios involving human relationships to the phenomenal world. The logic that made matter subject to uniform theorizing facilitated a crossing of boundaries between the human and nonhuman and became a persistent figure of explanation at the time when distinctions between the natural and the artificial were undergoing reformulation"--